RETRACTED: Teaching methodology with IT intensification and sociocultural theory - Chernova Natalya; Trukova Alena; Emelianova Margarita; Akhunzyanova Raisa (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001